Burnout syndrome and job satisfaction in health professionals - Yslado Méndez, Rosario Margarita (2019)
Objective: To estimate the functional relationships between burnout and job satisfaction in health professionals of two hospitals in Peru. Materials and methods: A quantitative, observational, correlational and cross-sectional research was carried out. Out of a study population of 620 health professionals, 177 (physicians, odontologists, pharmacists, psychologists, nurses, obstetricians, medical technologists, nutritionists and social workers) were interviewed. The Maslach Burnout Inventory (MBI) and the Job Satisfaction Scale (SL-SPC) were used as measuring instruments, showing adequate psychometric properties. Results: The high-burnout prevalence rate (TP) was 33.3 %. Using a structural equation analysis, a significant (AGFI = 0.946) and negative (structural coefficient = -0.62) relationship was found between burnout and job satisfaction in health professionals. The predominant dimension of burnout was depersonalization (37 % = 0.72 / (0.56 + 0.72 + 0.65)) and the predominant factor of job satisfaction was profits (35 % = 0.99 / (0.67 + 0.99 + 0.48 + 0.66)). Conclusions: There is a significant and negative functional relationship between burnout syndrome and job satisfaction. Burnout is a predictor of job satisfaction. No significant differences were found when comparing the high-burnout prevalence rate regarding the sociodemographic and work-related variables.